Sorption cold storage for thermal management of the battery of a hybrid vehicle. (November 2018) - Engel, Georg
Abstract: The transition towards e-mobility raises the necessity for a smart thermal management of vehicles. Waste heat becomes becomes sparsely available and only at low temperatures. In addition, the battery requires a narrow temperature window. Within the Austrian flagship-project Tes4seT, a novel thermal management based on a compact thermal storage is developed for hybrid vehicles. A sorption closed thermal energy storage system is designed for this application, targeting at both high energy density and high power density. In a hybrid vehicle, waste heat from the combustion engine may be used to charge the thermal storage. These requirements and the corresponding temperature levels motivate a storage system design involving a fixed bed heat exchanger coated with SAPO-34. A thermal energy storage system is designed, assembled and investigated experimentally in a dedicated test rig. The storage system including 2.5 kg of adsorbent is shown to provide cooling up to a power of 2 kW, and an average of 1 kW for a period of 30 minutes.